Nova's Master the LSAT - Kolby, Jeff (PrepCourse series., 2005)
To prepare properly for the LSAT, you must study problems that reflect the true LSAT format. The best way to do that is to study actual LSAT tests. Now, you can do that with this book! MASTER THE LSAT contains detailed solutions to numerous actual LSAT questions, carefully selected to illustrate every type of question that has appeared on the test in the past several years! These solutions will introduce you to numerous analytic techniques that will help you immensely not only on the LSAT but in law school as well.